Post Covid-19: the future of legal studies - Zulhuda, Sonny (2020)
This online forum discusses the big picture of future legal education, especially amid the emergence of technologies as well as the disruption of Covid-19 crisis. The thesis of the presentation is that the legal studies still and will keep changing in accordance with the changing circumstances. But one must always be clear of the foundation and philosophy of the legal education before any change should be effected.